2013
DOI: 10.3997/1873-0604.2014005
|View full text |Cite
|
Sign up to set email alerts
|

Global inversion of GPR traveltimes to assess uncertainties in CMP velocity models

Abstract: Velocity models are essential to process two‐ and three‐dimensional ground‐penetrating radar (GPR) data. Furthermore, velocity information aids the interpretation of such data sets because velocity variations reflect important material properties such as water content. In many GPR applications, common midpoint (CMP) surveys are routinely collected to determine one‐dimensional velocity models at selected locations. To analyse CMP data gathers, spectral velocity analyses relying on the normal‐moveout (NMO) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…RMSE in terms of the space that each parameter pair encompasses. Relative RMSE values above 16 % (the maximum is 189 %) 0 20 40 are plotted in yellow and not differentiated in the colorbar, because such antenna models generated signals that show noticeable differences to the measured signal in terms of amplitude and zero-crossings. Particles with hues of blue exhibit the best fits with little to no visual differences between each other and the reference trace.…”
Section: A Optimization Results and Analysismentioning
confidence: 99%
“…RMSE in terms of the space that each parameter pair encompasses. Relative RMSE values above 16 % (the maximum is 189 %) 0 20 40 are plotted in yellow and not differentiated in the colorbar, because such antenna models generated signals that show noticeable differences to the measured signal in terms of amplitude and zero-crossings. Particles with hues of blue exhibit the best fits with little to no visual differences between each other and the reference trace.…”
Section: A Optimization Results and Analysismentioning
confidence: 99%
“…In our implementation, we set ω=0.7298 and c1=c2=1.4962, which has proven to provide excellent convergence behaviour in different optimization problems (e.g., Eberhart and Shi ) including the inversion of geophysical travel time data (Tronicke et al . , ; Hamann and Tronicke ; Rumpf and Tronicke ).…”
Section: Methodsmentioning
confidence: 98%
“…Various studies have investigated the influence of these parameters on the convergence properties (e.g., Van den Bergh 2002;Elbeltagi, Hegazy, and Grierson 2005;Bratton and Kennedy 2007) and have demonstrated that results are rather insensitive to the swarm size. Following Hamann and Tronicke (2014), we use a swarm size 1.5 times the number of parameters, which shows reasonable convergence behaviour. On the other hand, the choice of ω, c 1 , and c 2 might critically influence the results and the performance of the PSO algorithm.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The rms velocity approximation accounts for variable velocities under the assumption of an offset to depth of investigation ratio (O/DOI) of smaller than 0.5 (Al‐Chalabi ; Castle ) and a horizontally layered medium (Schneider ; Wiggins ). As typical GPR field data fullfil these assumptions and show only minor errors in O/DOI ratio (Hamann and Tronicke ), we simply replace the constant velocity assumption in equation by the space and time dependent rms velocity approximation (equation ) resulting in rightt(x,y,z)2=t02+4(xx0)2+(yy0)2+(zz0)2vrms2right+4t0(zz0)vrms. …”
Section: Methodsmentioning
confidence: 99%